The Influence of Educational Content, Podcasts, and Patient Testimonials on Instagram on Generation Z's Treatment-Seeking Interest at M Hospital Jakarta - Maria Theresia Pinsasia; Rian Andriani; Didin Syarifuddin (International Journal of Marketing & Human Resource Research, 2026)
This study examines the influence of educational content, podcasts, and patient testimonials on Instagram on Generation Z's willingness to seek treatment at M Hospital Jakarta. The research employs a quantitative approach with a survey method involving 125 Generation Z respondents who actively use Instagram, selected through simple random sampling. Data were collected using validated and reliable questionnaires containing indicators for educational content, podcasts, patient testimonials, and treatment interest variables. Multiple linear regression analysis was used to determine the effect of each variable on treatment interest. The findings reveal that all three variables educational content, podcasts, and patient testimonials significantly influence Generation Z's interest in seeking treatment at M Hospital Jakarta. Educational content demonstrates a positive and significant effect (coefficient 0.298, p < 0.05), podcasts show a positive and significant impact (coefficient 0.352, p < 0.05), and patient testimonials exhibit a positive and significant influence (coefficient 0.287, p < 0.05). Simultaneously, these three variables account for 69.1% of the variance in treatment interest (R² = 0.691, F = 89.941, p < 0.001). These results indicate that health-related content designed attractively and educatively on social media, particularly Instagram, can enhance Generation Z's trust and motivation to utilize healthcare services, while strengthening hospital promotional strategies. This research provides valuable implications for hospitals in designing appropriate and effective social media-based promotional strategies to reach younger generations. Through engaging and educational content, podcasts, and patient testimonials, hospitals can increase treatment interest and build a positive image among Generation Z, who are increasingly active in the digital media landscape